Peran Intensitas Latihan dalam Hipertrofi Otot Skeletal - Irawati, Nur Ayu Virginia; Sylviana, Nova; Lubis, Leonardo (Jurnal Biomedika dan Kesehatan, 2024)
Endurance training, a form of physical activity that relies on continuous aerobic exercise and repetitive muscle contractions, is widely acknowledged for its positive effects on overall physical fitness. Aerobic exercise, an essential component of endurance training, has numerous benefits including improved cardiovascular and respiratory health, increased muscle endurance, and enhanced resistance against fatigue. It has also been found to contribute to skeletal muscles, potentially by stimulating the synthesis of proteins involved in muscle fiber formation. Although resistance exercise has been favored for promoting muscle growth, some suggests that aerobic exercise can also produce skeletal muscle hypertrophy comparable to that of resistance exercise if performed correctly. The duration, intensity, and specific type of aerobic exercise play important roles in determining skeletal muscle mass. The mammalian target of rapamycin (mTOR) known as a key regulator of muscle protein synthesis that associated with exercise activity. Several signaling pathways, such as Akt/mTOR and MAPK, are involved in controlling muscle protein synthesis during exercise. This review aimed to understand the impact of aerobic exercise intensity and other training parameters on skeletal muscle, to provide valuable insights for optimizing exercise programs and fostering muscle hypertrophy. In this review, we had systematically searched PubMed and Google Scholar from January 2013 to May 2023. Our result indicated that aerobic exercise can be expected to promote skeletal muscle hypertrophy and improve muscle mass and function. The regulation of skeletal muscle mass is complex, involving various signaling pathways such as mTOR, as well as the influence of hormones and growth factors.